Deep sternal wound infection and pectoralis major muscle flap reconstruction: A single-center 20-year retrospective study - Chen, Chen; Gao, Yu; Zhao, Demei; Ma, Zhouji; Su, Yunyan; Mo, Ran (Frontiers in Surgery, 2022)
Background: One of the most feared complications caused by median sternal incision is deep sternal wound infection (DSWI). DSWI leads to prolonged hospitalization, increased expected costs, re-entry into the ICU and other risks. Physicians disagree regarding the treatment of DSWI. Common treatment methods include povidone iodine irrigation, antibiotic irrigation, negative pressure wound therapy, and debridement, but it is difficult to completely and effectively cure DSWI. Recently, we have adopted the method of radical debridement and transposition of a pectoralis major muscle flap (PMMF) to treat DSWI patients and have achieved good results. Compared with traditional irrigation and dressing changes or debridement, the cure rate has been significantly improved. Methods: This study retrospectively analyzed all 14250 consecutive patients who underwent cardiac surgery in the Department of Cardiothoracic Surgery of Drum Tower Hospital from 2001–2020. Ultimately, 134 patients were diagnosed with DSWI. Thirty-one of them had recently undergone radical debridement and transposition of the PMMF in the cardiothoracic surgery or burns and plastic surgery departments because of DSWIs, while the remaining patients received conservative treatment or other methods of dressing debridement. Results: In total, 9824 patients were enrolled in the study between 2001 and 2020, of whom 134 met the DSWI criteria and 9690 served as controls. Body mass index (OR=1.08; P=0.02; 95% CI: 1.01~1.16) and repeat sternotomy (OR=5.93; P<0.01; 95% CI: 2.88~12.25) were important risk factors for DSWI. Of the 134 patients with DSWI, 31 underwent PMMF, and 103 served as controls. There were significant differences in CABG (P<0.01), valve replacement (P=0.04) and repeat sternotomy (P<0.01) between the case group and the control group. The postoperative extubation time (P<0.001), ICU time (P<0.001), total hospitalization time (P<0.001) and postoperative hospitalization time (P<0.001) in the PMMF group were significantly lower than those in the control group. The results of multivariate regression analysis showed that PMMF surgery is an important protective factor for the postoperative survival of DSWI patients (OR=0.12; P=0.04; 95% CI: 0.01~0.90). Conclusions: We describe PMMF treatment of DSWI and the achievement of good clinical results. This method can be used as routine therapy for DSWI after cardiac surgery.